Wehrlose Wahrheit: Die Christus bekennende Kirche inmitten der Vielfalt der Religionen Religionen - Stoevesandt, Hinrich (Zeitschrift für Theologie und Kirche, 2005)
The church, used to living in secular surroundings for a long time, now sees itself confronted with yet another challenge in the form of non-Christian religions. How can theology react to this situation? The author presents a critical outline of different approaches to a »theology of religions« which he places against a plea for the belief in »solus Christus«, bearing witness to the defenceless truth of the crucified Savior.